Poemas em cinza e ouro: O itinerário português de Ronald de Carvalho - Marques, Fernando Carmino; Pizarro, Jerónimo (Pessoa Plural, 2024)
In this article, focusing on the reception of Ronald de Carvalho’s poetry in Portugal, partic-ular attention is given to the poems that the Brazilian poet published between 1914 and 1921, especially through the magazine A Águia, as well as some critical reactions that his poetry elicited. Some of these poems were included in Poemas e Sonetos (1919), with notable variations. In the Appendices, there is a letter from Fernando Pessoa to Ronald de Carvalho about the book Luz Gloriosa (1913), which deserves to be republished (both the draft and the sent version), and a posthumous letter to the same recipient, written by Vitorino Nemésio. In this letter, the Azorean writer argues that Portugal and Brazil should unite in defending and promoting their common language, without disregarding the differences between their speakers.